Concise Total Syntheses of Pyrido[4, 3‐b]carbazole Alkaloids Using Copper‐Mediated 6π‐Electrocyclization. Issue 13 (13th April 2016) - Itoh, Tomoki; Abe, Takumi; Choshi, Tominari; Nishiyama, Takashi; Yanada, Reiko; Ishikura, Minoru
Abstract: Concise syntheses of 9‐methoxyellipticine, 3, 4‐dihydroellipticine (µ‐alkaloid D), 1, 2, 3, 4‐tetrahydroellipticine, 2‐methyl‐1, 2, 3, 4‐tetrahydroellipticine, olivacine, 3, 4‐dihydroolivacine, (±)‐guatambuine, and (±)‐janetine were developed starting from hexatriene intermediates readily obtained by Pd‐catalyzed tandem cyclization/cross‐coupling reaction of indolylborates. The route enables the facile construction of pyrido[4, 3‐ b ]carbazoles by Cu‐catalyzed 6π‐electrocyclization and subsequent transformation of the pyridocarbazole intermediates into pyrido[4, 3‐ b ]carbazole alkaloids. Abstract : Concise total syntheses of pyrido[4, 3‐ b ]carbazole alkaloids were accomplished using Cu‐catalyzed 6π‐electrocyclization of hexatriene as a key step.